Prohibition of the Use of Mosques as Campaign Venues: A Comparative Study of the Constitutional Court's Decision Number 65/PUU-XXI /2023 and Siy?sah Dusturiy?h - Siregar, Rahmat Insani; Khalid, Khalid (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2024)
Historically, politics and mosques have been two things that are difficult to separate. Even though it is noted that mosques were once a place of political activity, nowadays this has become pro-political. For the reason that the use of mosques as political activities is considered a form of violation in election contestation and has very high practical political value. Here the author is interested in discussing the dynamics of the ban on mosques as campaign venues before and after the Constitutional Court Decision Number 65/PUU-XXI/2023. This research aims to analyze the provisions prohibiting mosques as campaign venues before and after the Constitutional Court Decision Number 65/PUU-XXI/2023 along with several cases that have occurred. This research focuses on text and literature analysis, library research or library studies. In this research, the approach used is a normative approach. This approach is used to analyze the causes or legal provisions that prohibit campaigns in places of worship. The results of this research show that the prohibition on campaigning in places of worship is regulated in Article 285 of Law Number 7 of 2017 concerning General Elections. Then the Constitutional Court Decision Number 65/PUU-XXI/2023 further emphasized the prohibition on campaigning in places of worship without exception. So this is considered to minimize identity politics that could occur in the future. In the view of siyasah fiqh, holding political campaigns in mosques may be justified, as long as it does not violate the sharia rules established by the Prophet Muhammad SAW. However, it should be remembered that the principle of siy?sah fiqh emphasizes the avoidance of harm (loss) more than the achievement of benefits [Abstrak Dalam sejarahnya, politik dan masjid menjadi dua hal yang sulit dipisahkan. Meski tencatat bahwa masjid pernah menjadi tempat kegiatan politik namun dimasa sekarang hal tersebut menjadi pro-kotra. Dengan alasan bahwa penggunaan masjid sebagai kegiatan politik dianggap sebagai bentuk pelanggaran dalam kontestasi pemilu dan memiliki nilai politik praktis yang sangat tinggi. Disini penulis tertarik mendiskusikan tentang dinamika larangan masjid sebagai tempat kampanye sebelum dan sesudah adanya Putusan MK Nomor 65/PUU-XXI/2023. Penelitian ini bertujuan menganalisa tentang ketentuan larangan masjid sebagai tempat kampanye sebelum dan sesudah adanya Putusan MK Nomor 65/PUU-XXI/2023 disertai bebera kasus yang perneh terjadi. Penelitian ini berfokus pada analisis teks dan literatur library research atau studi kepustakaan. Dalam penelitian ini, pendekatan yang digunakan adalah pendekatan normatif. Metode pendekatan ini digunakan untuk menganalisis sebab atau ketentua hukum yang melarang kampanye di tempat ibadah. Hasil penelitian ini menunjukan bahwa larangan kampanye di tempat ibadah diatur pada pasal 285 Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum. Kemdian Putusan Mahkamah Konstitusi Nomor 65/PUU-XXI/2023 semakin menegaskan larangan tentang larangan kampanye di tempat ibadah tanpa pengecualian. Sehingga hal ini dianggap dapat meminimalisir politik indentitas yang dapat terjadi di kemudian hari. Dalam pandangan fiqih siy?sah, melakukan kampanye politik di masjid mungkin dapat dibenarkan, selama tidak melanggar aturan syariat yang telah ditetapkan oleh Nabi Muhammad SAW. Namun, perlu diingat bahwa prinsip fiqih siy?sah menekankan pada penghindaran mudharat (kerugian) lebih daripada pencapaian manfaat.]